Effect of Workload and Work Stress on Employees Performance Through Job Satisfaction as Intervening Variable in Rubber Plantation, Serdang II District, PT. Perkebunan Nusantara III - Watson AP Manalu; Yusniar Lubis; Syaifuddin Syaifuddin (Institute of Computer Science (IOCS), 2022)
This study to examine the effect of workload on job satisfaction, workstress on job satisfaction, examine the effect of workload and work stress on job satisfaction, workload on employee performance, work stress on employee performance, job satisfaction on employee performance, workload and work stress on employee performance through job satisfaction in Rubber Plantation Serdang II District, PTPN III. The sample in this study are 82 people. The analytical method used in this research using multiple linear regression analysis. The result of the direct influence test shows that workload has a negative effect on job satisfaction, work stress has a negative effect on job satisfaction, workload and work stress have an influence on job satisfaction, workload has a negative effect on employee performance, work stress has a negative effect on employee performance, job satisfaction has a positive effect on employee performance and the effect of workload, job stress and job satisfaction has a positive effect on employee performance. The indirect effect that occurs in this study is that job satisfaction is only able to become a pseudo-mediator on employee performance.